Isolated cerebellar progressive multifocal leukoencephalopathy after allogeneic bone marrow transplantation: focus on imaging. Issue 6 (December 2021) - Mazzai, Linda; Facchinelli, Davide; Borghero, Carlo; Vitale, Valerio; Ruggeri, Marco; Iannucci, Giuseppe
Introduction: Progressive multifocal leukoencephalopathy (PML) is caused by JC virus opportunistic infection in the setting of immunodeficiency. Typical imaging features are multifocal and asymmetric lesions within supratentorial subcortical white matter in parieto-occipital regions. Case description: A 47-year-old patient experienced a relapse of acute myeloid leukemia 21 months after hematopoietic stem cell transplantation. He also had visual impairment and magnetic resonance imaging showed an isolated cerebellar lesion without mass effect or enhancement. Common opportunistic infections and leukemic central nervous system involvement were excluded by cerebrospinal fluid (CSF) analysis. Given the worsening clinical and radiologic scenario, PML was suspected, and CSF protein chain reaction analysis was positive for JC virus. Conclusions: Given its potential curability, PML should be thoroughly investigated in patients with hematologic neoplasms and atypical isolated cerebellar presentation.